Metodologia de otimização via simulação para dimensionamento dainfraestrutura de sistemas logísticos intermodais para o escoamento decommodities - Ingrid Machado Silveira (2017)
Various productive activities, such as mining and the agricultural industry, have a large part of their production destined for international trade. In this way, it is necessary to dispose of its products over long distances, from its point of production to the point of consumption. For this, it is generally used intermodal transport, which includes the modalities of road, rail and waterway. In this system, the efficient use of logistical resources is of paramount importance for reducing costs and raising the level of service provided. This work aims to propose an optimization methodology through simulation for the design of part of the infrastructure of an intermodal logistics system for the transportation of commodities, aiming at minimizing logistics costs and, consequently, maximizing the use of resources. It seeks to optimize logistics costs related to the design of warehouses and train compositions. The optimization step was performed using two distinct tools: an optimizer available in commercial simulation package and a heuristic developedspecifically for this type of problem. These tools were analyzed, aiming to verify an adequacy to the same solution of the problem under study. Finally, a sensitivity analysis was carried out in order to obtain some important considerations about the logistic system studied.